EFFECT OF COUNSELLING ON FREQUENCY AND SEVERITY OF NAUSEA AND VOMITING IN PREGNANCY (NVP) - Luh Sukeningsih; Baksono Winardi; Tiyas Kusumaningrum (Indonesian Midwifery and Health Sciences Journal, 2020)
ABSTRACTBackground: Nausea and vomiting are commonly during early pregnancy. Nausea and vomiting significantly decrease in quality of life. Objective:This study aimed to explain the effect of counseling on the frequency and level of nausea and vomiting in pregnant women. Method: This was a quasi-experimental study with a non randomized control group pretest posttest design. The control group was 37 people and the experimental group were 37 people. The control group only received a standard ANC, the experimental group received nausea and vomiting counseling in pregnancy. The independent variables was counselling based on Roy Adaptation Model, the dependent variable was frequency and level severity of nausea and vomiting. The research instrument used was a questionnaire and counseling. Data analysis used univariate and bivariate analysis (Wilcoxon Signed Rank Test and Mann Whitney). Results: The experimental group experienced decreased in frequency and level of nausea, while control group did not change. Statistical Mann Whitney test results obtained p value of nausea frequency of 0.018, and p value of frequency of vomit 0.000 and p value of levels of nausea and vomiting 0.034 which showed that there were differences in the experimental group compared to the control group. Conclusion: There is an effect of counseling Roy Adaptation Model to the frequency and level of nausea vomiting in pregnancy